Mental Health Disparities Among LGBTQ+ Youth and The Strategies to Promote Their Well-Being - Sneha Sunil; Masoud Mohammadnezhad (Journal of Public Health International, 2024)
Introduction Compared to their heterosexual counterparts, cisgender LGBTQ+ youth are more likely to experience numerous mental health conditions, for instance, suicidal ideation, stress, and anxiety. This study aimed to explore mental health disparities among LGBTQ+ youth while identifying strategies to promote their well-being. Methodology Incorporating a systematic approach, studies were selected according to the predefined inclusion criteria, ensuring recentness and relevance. Five databases were systematically searched while the PRISMA flowchart was employed for illustrating the systematic selection process. The PEO framework directed the study selection. Thematic analysis was applied to identify themes that were related to the study aim. Results Five themes were emerged including policy changes and legal frameworks, contextual and cultural factors, family and social support, underlying factors of mental health, and healthcare services access. The synthesis of the literature uncovers the multifaceted relationship between cultural and contextual factors and policy changes, social and family support and healthcare services. The study also underlines the importance of implementing an intersectional minority stress model for comprehensively understanding mental health disparities among LGBTQ+ youth. Conclusion The results emphasize the importance of ongoing research in policy alterations, accessibility to healthcare, and creating supportive surroundings to tackle differences in mental health. Recognizing the complexity of these issues, this paper requires an in-depth examination that considers intersecting factors, promotes inclusivity, and involves long-term studies in providing mental health support to enhance the well-being of LGBTQ+ young individuals.
Keywords: Mental health